Veggies4myHeart— A digital game to promote vegetable consumption in preschool children - Pereira Braga Pontes, Cátia Sofia (2022)
Vegetable consumption is particularly low in childhood and is one of the main concerns about diet in this age range. Vegetable consumption is associated with better cardiovascular health and the prevention of other chronic non-communicable diseases. Therefore, it is important to find strategies to promote vegetable consumption at early ages, since eating habits established in childhood tend to persist into adulthood. The purpose of this study is to evaluate the impact of using a digital game on knowledge about vegetables and his consumption, in preschool children.